2019
DOI: 10.1097/scs.0000000000005277
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Craniofacial Bone Reconstruction With SmartBone on Demand

Abstract: This is a report of a 34-year-old male lacking of bone development in the frontal and orbital part of the skull due to a surgical removal of a right orbital-front osteoma at the age of 5. The integrity of the craniofacial district was important for the young patient also for social acceptance and self-esteem. Based on computed tomography patient images, a skull model was reconstructed, both digitally and on 3-dimensional real model, to best design the needed bone graft. Defect wide extension and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Conditions required different treatment for the second site. The calcium phosphosilicate did not possess the same mechanical characteristics as those of a xenogenic bone graft, but it was very suitable for socket preservation [25] provided that the treated region received good coverage in order to achieve the proper revascularization of grafts from periosteal vessels. Having a patient with different lesions allowed us to validate the strategy of adapting our choice of biomaterial to the characteristics of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions required different treatment for the second site. The calcium phosphosilicate did not possess the same mechanical characteristics as those of a xenogenic bone graft, but it was very suitable for socket preservation [25] provided that the treated region received good coverage in order to achieve the proper revascularization of grafts from periosteal vessels. Having a patient with different lesions allowed us to validate the strategy of adapting our choice of biomaterial to the characteristics of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…At the site where we extracted Region 35, we proceeded to implant xenohybrid graft SmartBone (SB), developed and manufactured by Industrie Biomediche Insubri SA (IBI-SA) via a proprietary process that improves the properties of naturally derived biomaterials [23]. SB was specifically developed for regenerative-medicine applications, and has a long track record of clinical applications [24][25][26][27][28]. SB is composed of a decellularized-bovine-bone matrix reinforced with bioresorbable aliphatic polyesters and RGD-containing collagen fragments [23,29], where RGD is the tripeptide sequence ArginylGlycylAspartic acid that is the most common peptide motif responsible for cell adhesion to the extracellular matrix.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The CBCT images were used to create a virtual upper jaw model to support graft design. Further, in order to demonstrate the goodness of the digital design, files have been replicated and verified in a 3D stereolithographic model [16]. This solid model was mounted onto an articulator.…”
Section: Methodsmentioning
confidence: 99%
“…SmartBone ® (SB ® ), a xeno-hybrid developed and manufactured by Industrie Biomediche Insubri SA (Switzerland), was devised according to a new concept in composite approach, building on a base of bovine decellularized bone-derived mineral matrix, reinforced with bioresorbable aliphatic polymers and RGD-containing collagen fragments derived from animal-sourced gelatin (RGD is the acronym of the tripeptide arginine-glycine-aspartic acid). Such a new concept of biomaterial assembly allows the patient's cells to grow quickly and efficiently into the graft, while its biopolymers degrade, providing osteoconduction, supporting osteogenesis and finally ensuring perfect integration via complete remodeling [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This composite biomaterial resembles human bone microstructure and provides macro-scale properties: an adequate-sized open porosity with a combined rigid-elastic behavior, in combination with surface properties, which ensures cell viability and rapid tissue integration.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a 2018 study reported a significant bone volume increase of 40% four months postop [42]. A study from 2019 showed an increment of 16 cc of new bone on the treated area of an important craniofacial district [46], and a study in traumatology showed evidence of not only bone regeneration but also anatomically selective remodeling [45].…”
Section: Introductionmentioning
confidence: 99%